2007
DOI: 10.1002/oa.954
|View full text |Cite
|
Sign up to set email alerts
|

Morphological changes in the shape of the non‐pathological bony knee joint with age: a morphometric analysis of the distal femur and proximal tibia in three populations of known age at death

Abstract: This study examines possible morphological variation in the knee joint of Homo sapiens with increasing age in ostensively healthy and non-pathological distal femora and proximal tibiae. Throughout the lifetime of each individual, the hard tissue of the knee undergoes considerable remodelling as a response to biomechanical stresses, changes in bone microarchitecture and reduction of bone mineral content as a concomitant of ageing. The knee is also subject to greater levels of degenerative joint disease than any… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 53 publications
1
15
0
Order By: Relevance
“…Recent geometric morphometric studies exploring age changes in the proximal tibia have revealed that although age-dependent shape variation is apparent and significant, inter-population and sex-related shape differences are considerably more important [6,9]. In the tibial shaft, where we saw the most marked SD, cross-sectional geometry age changes take the form of continuous expansion during adulthood (for review see [70]).…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Recent geometric morphometric studies exploring age changes in the proximal tibia have revealed that although age-dependent shape variation is apparent and significant, inter-population and sex-related shape differences are considerably more important [6,9]. In the tibial shaft, where we saw the most marked SD, cross-sectional geometry age changes take the form of continuous expansion during adulthood (for review see [70]).…”
Section: Discussionmentioning
confidence: 88%
“…The issue of human tibia design has been studied extensively, but research has predominantly dealt only with shape variation of the shaft [25]. A few studies have focused on the shape of the articular ends [69] and even fewer have considered the whole tibial external geometry [10,11]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The few studies that have assessed distal femur or proximal tibia shape have assessed it in the context of knee osteoarthritis or clinical studies looking to predict outcome of interventions based on bone morphology. Interestingly all these studies noted differences in the femoral intercondylar notch shape associated with either osteoarthritis or the success of cruciate ligament reconstruction, and many proposed that this may arise due to differences in cruciate ligament attachment [45][46][47][48]. Differences in the shape of the distal femur based on age and sex have also been reported elsewhere [46].…”
Section: Accepted Manuscriptmentioning
confidence: 86%
“…Three‐dimensional Cartesian coordinates of landmarks were digitized on the joint surfaces using a Microscribe® GLS digitizing system (EMicroscribe Inc) (Figures a–c). Landmarks for the distal femur were based on those used by Stevens & Strand Viðarsdóttir (). These landmark data were then superimposed using generalized Procrustes analysis, which removes all scale and translational variation from the data (Goodall, ); size information in the form of centroid size was retained as an independent variable.…”
Section: Methodsmentioning
confidence: 99%